Live high + Train low: Thinking in terms of an optimal hypoxic dose - Wilber, R. L. (International Journal of Sports Physiology and Performance, 2007)
"Live high-train low" (LH+TL) altitude training allows athletes to "live high" for the purpose of facilitating altitude acclimatization, as characterized by a significant and sustained increase in endogenous erythropoietin and subsequent increase in erythrocyte volume, while simultaneously enabling them to "train low" for the purpose of replicating sea-level training intensity and oxygen flux, thereby inducing beneficial metabolic and neuromuscular adaptations. In addition to natural/terrestrial LH+TL, several simulated LH+TL devices have been developed including nitrogen apartments, hypoxic tents, and hypoxicator devices. One of the key issues regarding the practical application of LH+TL is what the optimal hypoxic dose is that is needed to facilitate altitude acclimatization and produce the expected beneficial physiological responses and sea-level performance effects. The purpose of this review is to examine this issue from a research-based and applied perspective by addressing the following questions: What is the optimal altitude at which to live, how many days are required at altitude, and how many hours per day are required? It appears that for athletes to derive the hematological benefits of LH+TL while using natural/terrestrial altitude, they need to live at an elevation of 2000 to 2500 m for =4 wk for =22 h/d. For athletes using LH+TL in a simulated altitude environment, fewer hours (12-16 h) of hypoxic exposure might be necessary, but a higher elevation (2500 to 3000 m) is required to achieve similar physiological responses.